(untitled) - Henderson, James W. (Victoria, Australia, 2005)
Health Economics and Policy is a basic introduction to the microeconomics of health, health care, and health policy. This edition demonstrates how economic principles apply to health-related issues. It explains the social, political, and economic contexts of health care delivery and explores the changing nature of health care. Students learn to analyze public policy from an economic perspective. While the text was written for non-economics majors, it includes enough economic content to challenge majors.
Keywords: Medical care; Economic aspects